Efficient microwave to optical photon conversion: An electro-optical realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G. L. (Optica, 2016)
Linking classical microwave electrical circuits to the optical telecommunication band is at the core of modern communication. Future quantum information networks will require coherent microwave-to-optical conversion to link electronic quantum processors and memories via low-loss optical telecommunication networks. Efficient conversion can be achieved with electro-optical modulators operating at the single microwave photon level. In the standard electro-optic modulation scheme, this is impossible because both up- and down-converted sidebands are necessarily present. Here, we demonstrate true single-sideband up- or down-conversion in a triply resonant whispering gallery mode resonator by explicitly addressing modes with asymmetric free spectral range. Compared to previous experiments, we show a 3 orders of magnitude improvement of the electro-optical conversion efficiency, reaching 0.1% photon number conversion for a 10 GHz microwave tone at 0.42 mW of optical pump power. The presented scheme is fully compatible with existing superconducting 3D circuit quantum electrodynamics technology and can be used for nonclassical state conversion and communication. Our conversion bandwidth is larger than 1 MHz and is not fundamentally limited.
CRIS-Team Scopus Importer:2021-06-29

Efficient single sideband microwave to optical conversion using a LiNbO3 WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dimitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Interfacing transitions of different alkali atoms and telecom bands using one narrowband photon pair source - Schunk, Gerhard; Vogl, Ulrich; Strekalov, Dmitry V.; Förtsch, Michael; Sedlmeir, Florian; Schwefel, Harald; Göbelt, Manuela; Christiansen, Silke; Leuchs, Gerd; Marquardt, Christoph (Optica, 2015)
Quantum information technology strongly relies on the coupling of optical photons with narrowband quantum systems, such as quantum dots, color centers, and atomic systems. This coupling requires matching the optical wavelength and bandwidth to the desired system, which presents a considerable problem for most available sources of quantum light. Here we demonstrate the coupling of alkali dipole transitions with a tunable source of photon pairs. Our source is based on spontaneous parametric downconversion in a triply resonant whispering gallery mode resonator. For this, we have developed novel wavelength-tuning mechanisms that allow a coarse tuning to either the cesium or rubidium wavelength, with subsequent continuous fine-tuning to the desired transition. As a demonstration of the functionality of the source, we performed a heralded single-photon measurement of the atomic decay. We present a major advance in controlling the spontaneous downconversion process, which makes our bright source of heralded single photons now compatible with a plethora of narrowband resonant system
Keywords: Atomic; Quantum communications; Quantum optics; Spectroscopy

Nonlinear power dependence of the spectral properties of an optical parametric oscillator below threshold in the quantum regime - Shafiee, Golnoush; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schunk, Gerhard; Vogl, Ulrich; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (New Journal of Physics, 2020)
Photon pairs and heralded single photons, obtained from cavity-assisted parametric down conversion (PDC), play an important role in quantum communications and technology. This motivated a thorough study of the spectral and temporal properties of parametric light, both above the optical parametric oscillator (OPO) threshold, where the semiclassical approach is justified, and deeply below it, where the linear cavity approximation is applicable. The pursuit of a higher two-photon emission rate leads into an interesting intermediate regime, between above OPO threshold and very low pump power, where the OPO still operates considerably below the threshold but the nonlinear cavity phenomena cannot be neglected anymore. Here, we investigate this intermediate regime and show that the spectral and temporal properties of the photon pairs, as well as their emission rate, may significantly differ from the widely accepted linear model. The observed phenomena include frequency pulling and broadening in the temporal correlation for the down-converted optical fields. These factors need to be taken into account when devising practical applications of the high-rate cavity-assisted spontaneous PDC sources.
CRIS-Team WoS Importer:2020-08-21

Nonlinear single sideband microwave to optical conversion using an electro-optic WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2016)
Nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band is achieved within a crystalline whispering gallery mode resonator, reaching 0.1% photon number conversion efficiency with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Single sideband microwave to optical photon conversion-an electro-optic realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2017)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator.
CRIS-Team Scopus Importer:2021-06-29

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Vogl, Ulrich; Dirmeier, Thomas; Shafiee, Golnoush; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald; Gehring, Tobias; Andersen, Ulrik Lund; Leuchs, Gerd; Marquardt, Christoph (Optica, 2019)
Squeezed vacuum states enable optical measurements below the quantum limit and hence are a valuable resource for applications in quantum metrology and also quantum communication. However, most available sources require high pump powers in the milliwatt range and large setups that hinder real-world applications. Furthermore, degenerate operation of such systems presents a challenge. Here, we use a compact crystalline whispering gallery mode resonator made of lithium niobate as a degenerate parametric oscillator. We demonstrate about 1.4 dB noise reduction below the shot-noise level for only 300 mu W of pump power in degenerate single-mode operation. Furthermore, we report a record pump threshold as low as 1.35 mu W. Our results show that the whispering gallery-based approach presents a promising platform for a compact and efficient source for nonclassical light. (c) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-12-06